The oligodendrocyte-enriched orphan G protein-coupled receptor Gpr62 is dispensable for central nervous system myelination - Curtis M. Hay (BMC, 2021)
Abstract Background Myelination is a highly regulated process in the vertebrate central nervous system (CNS) whereby oligodendrocytes wrap axons with multiple layers of insulating myelin in order to allow rapid electrical conduction. Establishing the proper pattern of myelin in neural circuits requires communicative axo-glial interactions, however, the molecular interactions that occur between oligodendrocytes and axons during developmental myelination and myelin maintenance remain to be fully elucidated. Our previous work identified G protein-coupled receptor 62 (Gpr62), an uncharacterized orphan g-protein coupled receptor, as being selectively expressed by mature oligodendrocytes within the CNS, suggesting a potential role in myelination or axoglial interactions. However, no studies to date have assessed the functional requirement for Gpr62 in oligodendrocyte development or CNS myelination. Methods To address this, we generated a knockout mouse strain lacking the Gpr62 gene. We assessed CNS myelination during both postnatal development and adulthood using immunohistochemistry, electron microscopy and western blot. In addition, we utilized AAV-mediated expression of a tagged Gpr62 in oligodendrocytes to determine the subcellular localization of the protein in vivo. Results We find that virally expressed Gpr62 protein is selectively expressed on the adaxonal myelin layer, suggestive of a potential role for Gpr62 in axo-myelinic signaling. Nevertheless, Gpr62 knockout mice display normal oligodendrocyte numbers and apparently normal myelination within the CNS during both postnatal development and adulthood. Conclusions We conclude that in spite of being well-placed to mediate neuronal-oligodendrocyte communications, Gpr62 is overall dispensable for CNS myelination.